Post-stroke patients functional task characterization through accelerometry data for rehabilitation intervention and monitoring - Claudia S. Silva (2011)
An increasing ageing society and consequently rising number ofpost-stroke related neurological dysfunction patients are forcing therehabilitation field to adapt to ever-growing demands. Compensatorymovements related to available motor strategies, can be observed inpost-stroke patients when performing functional tasks due to apathological synergy as in reaching for an object. Studies of post-strokemotor recovery suggest that such maladaptive strategies may limit theplasticity of the nervous system to enhance neuromotor recovery.Strategies for rehabilitation protocols monitoring and validation arepresently a necessity, moreover considering data recording is oftenabsent of the rehabilitation process or subjective in nature.Characterization strategies of patient performance during functional taskare key aspects for clinical protocols validation, progress monitoring andmethodologies comparison. This project seeks to characterize patientsupper limb performance through accelerometry, gathered with a lowcostwearable system, for compensatory movement avoidance throughfeedback response.